Rekonstruksi Penegakan Hukum Lingkungan terhadap Kejahatan Ekologis: Studi Pendekatan Sustainable Development Goals (SDGs) - Taupik Hidayat; Muhammad Abdul Zalil; Ade Aspandi; Fahmi Muhammad Ilham; Anisyahnia Rahar Tantri (Fakultas Hukum, Universitas Warmadewa, 2026)
Ecological crimes pose a serious threat to environmental sustainability, affecting both human life and ecosystem stability. Normatively, Indonesia has established a comprehensive legal framework through Law Number 32 of 2009 on Environmental Protection and Management, which regulates environmental protection and adopts the principle of strict liability. However, there is a significant gap between legal norms (das sollen) and empirical reality (das sein), as reflected in the major floods and landslides in Sumatra during 2025–2026, which resulted in substantial casualties and environmental damage. Studies indicate that these disasters were not solely caused by natural factors but were also driven by deforestation and weak environmental governance. This study aims to analyze the normative construction of environmental law enforcement and examine the causes of the gap in its implementation within the framework of the Sustainable Development Goals (SDGs). This research uses a normative juridical method with statutory and conceptual approaches. The findings reveal that weak law enforcement is caused by ineffective supervision, weak corporate accountability, and the lack of integration of sustainable development principles into legal policies. Therefore, a reconstruction of environmental law enforcement is necessary, emphasizing a more progressive, integrative, and ecologically just approach.